Health services financing and delivery: analysis of policy options for Dubai, United Arab Emirates - Hamidi S (Dove Medical Press, 2015)
Samer Hamidi School of Health and Environmental Studies, Hamdan Bin Mohammed Smart University, Dubai, United Arab Emirates Introduction: A national health account (NHA) provides a systematic approach to mapping the flow of health sector funds within a specified health system over a defined time period. This article attempts to present a profile of health system financing in Dubai, United Arab Emirates using data from NHAs, and to compare the functional structures of financing schemes in Dubai with schemes in Qatar and selected member countries of the Organization for Economic Cooperation and Development (OECD). Methods: The author analyzed secondary data published in NHAs of Dubai and Qatar and data collected by the OECD countries and publicly available from Eurostat (Statistical Office of the European Union) of 25 OECD countries for comparative analysis. All health financing indicators used were as defined in the international System of Health Accounts (SHA). Results: In Dubai, spending on inpatient care was the highest-costing component, with 30% of current health expenditures (CHE). Spending on outpatient care was the second highest-costing component and accounted for about 23% of the CHE. Household spending accounted for about 22% of CHE (equivalent to US$187 per capita), compared to an average of 20% of CHE of OECD countries. Dubai spent 0.02% of CHE on long-term care, compared to an average of 11% of CHE of OECD countries. Dubai spent about 6% of CHE on prevention and public health services, compared to an average of 3.2% of CHE of OECD countries. Conclusion: The findings point to potential opportunities for growth and improvement in several health policy issues in Dubai, including increasing focus and funding of preventive services; shifting from inpatient care to day surgery, outpatient, and home-based services and strengthening long-term care; and introducing cost-containment measures for pharmaceuticals. More investment in the translation of NHA data into policy is suggested for future researchers. Keywords: health finance schemes, health delivery, health policy